Identification of Critical Path Changes and Concurrent Delays Using EDAM Method for Building Project - Zetta Rasullia Kamandang (Institut Teknologi Adhi Tama Surabaya, 2020)
Achieving a project whose punctually in completion date and duration is one of the main purposes of the project planning. However, avoiding the issue of the delay is hard to do. Delays itself commonly divided into three types, EN, EC and NE delays that represent the contribution of each project parties. Furthermore, the concurrent delay is at different levels that often use as a tool against each other parties. In term of preventing the time-frame problems, the critical path method (CPM) is widely applied. In the delay analysis technique, the EDAM method employs CPM to identify the critical path changes and the occurred concurrent delays. Implementing a six-floor building as-planned schedule and its delays information as a case study, this research results show that the critical path of the building has changed eight times and the concurrent delay occurred on the first change with six days of delays. By identifying the critical path change, project parties are expected to be able to prevent continuously delays by escalating the work progress. Furthermore, the information about concurrent delays would be essential in avoiding disputes regarding this issue. Project parties would be aware of their contribution to critical path changes by knowing their caused delay in that time period.